Therapeutic interventions of remdesivir in diabetic and nondiabetic COVID‐19 patients: A prospective observational study conducted on Pakistani population. Issue 12 (11th August 2021) - Qureshi, Qiadat Hasnain; Ashraf, Taimoor; Rehman, Kanwal; Khosa, Muhammad Kaleem; Akash, Muhammad Sajid Hamid
Abstract: We aimed to investigate the interventions of remdesivir in both diabetic and nondiabetic individuals who were suffering from a severe infection of novel coronavirus disease (COVID‐19). In this study, we aimed to explore the relationship between therapeutic effectiveness of remdesivir and complications of diabetes mellitus by observing the recovery period among diabetic and nondiabetic patients associated with COVID‐19 infection. A total of 850 COVID‐19 patients were recruited for this study, out of which 48% were diabetic and 52% were nondiabetics. The results of this study indicated that nondiabetic individuals administered with remdesivir recovered from COVID‐19 within 10 days showing a 95% confidence interval ( p  < 0.01), while the diabetic individuals recovered in 15 days. Nondiabetic patients administered with remdesivir exhibited higher chances of clinical improvement at 15th day than those who were associated with diabetes. Remdesivir administration improved the levels of various biochemical parameters, such as C‐reactive protein, lactate dehydrogenase, d ‐Dimer, and ferritin both in diabetic and nondiabetic patients. However, a significant improvement ( p  < 0.01) was seen in the level of biochemical parameters among nondiabetic patients as compared to that of diabetic patients administered with remdesivir treatment. In the end, it was concluded that remdesivir could be considered as a possible therapeutic agent in the treatment of COVID‐19 both in diabetic and nondiabetic situations. However, diabetic patients showed a delayed recovery as compared with that of nondiabetic patients, in which the recovery rate was high. Highlights: 1. Remdesivir can be considered as possible therapeutic agent for the treatment of COVID‐19 2. COVID‐19 patients having diabetes mellitus showed a delayed recovery when treated with remdesivir as compared to non‐diabetic COVID‐19 patients. 3. Non‐diabetic patients treated with remdesivir showed a faster recovery as compared with that of diabetic COVID‐19 patients.